Hubungan Kadar Inherent Mosture (IM) Terhadap Nilai Kalori Batubara - Maris, Gustri Yanda (ALKIMIA, 2019)
ABSTRACT Inherent Moisture (IM) is water contained in coal when coal is formed. IM is specifically found in the internal pore structure of coal and has a vapor pressure lower than normal vapor pressure. IM levels are considered as the basic characteristics of coal. High IM levels correlate with calorific value. The higher IM levels, the lower the caloric value. Calorific value is one of the main parameters in determining the quality of coal. The higher the calorific value, the higher the heat produced by coal. The purpose of this observation is to determine the relationship of Levels of Inherent Moisture (IM) to the calorific value of coa l Keywords : Coal, Correlation, Inherent Moisture, Linear Regression.